2019
DOI: 10.18535/ijsrm/v7i2.cs01
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality Technology to teach Gen Z students about Construction Safety: A Pilot Study

Abstract: This pilot study was conducted to investigate the effectiveness of using Virtual Reality (VR) technologies to teach the "Generation Z" (GenZ) students about construction safety as part of the Construction Science and Management (CSM) program at Tuskegee University.  Research shows that the "Technology Generation" or GenZ students are not satisfied with the traditional pedagogical methodology; rather they demand new hands-on tech-heavy immersive learning experience. In this direction, Virtual Reality is propell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This paper is a continuation of an earlier research study conducted to investigate the application of Virtual Reality (VR) based games for teaching construction safety to Gen Z students (Dastider, 2019). As part of this research, the students enrolled in the Construction Safety class were first exposed to the traditional 2D teaching aids, demonstrating construction hazards, and then to few commercially available VR safety games.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is a continuation of an earlier research study conducted to investigate the application of Virtual Reality (VR) based games for teaching construction safety to Gen Z students (Dastider, 2019). As part of this research, the students enrolled in the Construction Safety class were first exposed to the traditional 2D teaching aids, demonstrating construction hazards, and then to few commercially available VR safety games.…”
Section: Introductionmentioning
confidence: 99%
“…The research concluded that VR technologies have huge potential as an alternative teaching methodology for Gen Z students because they can provide the real life experience similar to jobsite visit without the potential liability that may arise on a construction site. However, the study also found that, one major challenge with implementing VR in a classroom is lack of customized construction safety related VR content (Dastider, 2019). In order to create customize VR construction safety content the team reached out to several commercial developers; however it became quickly evident that commercial developers are too expensive for pedagogical modules development.…”
Section: Introductionmentioning
confidence: 99%